DAYA DUKUNG AIR DAN LAHAN PERTANIAN KAWASAN AEROCITY KOTA BANJARBARU - Anggara Putra Yudha; Syarifuddin Kadir (Universitas Lambung Mangkurat, 2021)
This study was purpose to analyze carrying capacity water and agricultural land in Aerocity region of Banjarbaru. The method used refers to the Ministry of Environment No. 17 of 2009 concerning Guidelines for Determination of Environmental Carriying Capacity. The main component in this study determines the supply and demand aspects of water and agricultural land. The results showed that the analyze of water carrying capacity in Aerocity region of Banjarbaru showed that the supply of water in 2017 was 104,453,637.9 m3 / Year while the water demand was 66,747,200 m3 / Year. The refore the water carrying capacity status in the Aerocity of Banjarbaru has a surplus because the supply of water greater than water demand, while the results of the Analyze Agricultural Land Capacity in the Aerocity of Banjarbaru show that based on the planned spatial pattern of agricultural land area of Aerocity region is 8.75 ha, while demand for agricultural land is 17,395,989 ha. Therefore, the carrying capacity of agricultural land in Aerocity of Banjarbaru has deficit (deficiency) because land supply less than demand of land.Keywords: Carrying capacity of water; Carrying capacity of agriculture land; Aerocity